Energetics of ion competition in the DEKA selectivity filter of neuronal sodium channels - Boda, D.; Leaf, G.; Fonseca, J.; Eisenberg, B. (Condensed Matter Physics, 2015)
The energetics of ionic selectivity in the neuronal sodium channels is studied. A simple model constructed for the selectivity filter of the channel is used. The selectivity filter of this channel type contains aspartate (D), glutamate (E), lysine (K), and alanine (A) residues (the DEKA locus). We use Grand Canonical Monte Carlo simulations to compute equilibrium binding selectivity in the selectivity filter and to obtain various terms of the excess chemical potential from a particle insertion procedure based on Widom's method. We show that K⁺ ions in competition with Na⁺ are efficiently excluded from the selectivity filter due to entropic hard sphere exclusion. The dielectric constant of protein has no effect on this selectivity. Ca²⁺ ions, on the other hand, are excluded from the filter due to a free energetic penalty which is enhanced by the low dielectric constant of protein. Проведено дослiдження енергетики iонної селективностi в нейронних каналах натрiю. Використано просту модель, сконструйовану спецiально для селективного фiльтру. Селективний фiльтр канального типу мiстить залишки аспарату (D), глютамату (E), лiзину K) та аланiну (A) (область DEKA). Використано моделювання методом Монте Карло у великому канонiчному ансамблi для обчислення селективностi рiвноважного зв’язування у селективному фiльтрi i для отримання рiзних членiв надлишкового хiмiчного потенцiалу в результатi процедури вставляння частинок на основi методу Вiдома. Показано, що iони K ⁺ у суперництвi з Na⁺ ефективно вилучаються з селективного фiльтра за рахунок ентропiйного виключення твердих сфер. Дiелектрична проникнiсть протеїну не має жодного впливу на дану селективнiсть. З iншого боку, iони Ca²⁺ вилучаються з фiльтра за рахунок вiльного енергетичного “пенальтi”, що пiдсилюється низькою дiелектричною проникнiстю протеїну.